Shakespearean allusions and reminiscences in “The Aristos” and “The French Lieutenant’s Woman” by J.R. Fowles - Drozdova Maria Sergeevna (Studia Humanitatis, 2017)
The paper focuses on the strategies to realize the creative potential of Shakespeare’s legacy in “The Aristos” and “The French Lieutenant’s Woman” by John Fowles. The paper deals with John Fowles’s reminiscences and allusions to Shakespeare’s work aiming to trace the creative potential strategies in “The Aristos” and “The French Lieutenant’s Woman”. The author uses the literary hermeneutics and reception-aesthetics methods. The present paper has E.V. Abramovskikh’s theory and typology of creative reception developed by the author of the paper. The major feature of Shakespearean creative reception in Fowles’s works is the fact that Fowles regards Shakespeare as a dramatic poet and uses mainly the playing strategy of postmodernist type creative reception.